Distributional Impacts of Carbon Pricing on Households - Carbon Pricing Leadership Coalition (World Bank, Washington, DC, 2020)
Carbon pricing policies that are aligned with the Paris Agreement objectives will have positive and negative socio-economic impacts on society. Impacts of unabated climate change are expected to disrupt economic development and disproportionally affect the poorest parts of the population, especially in lower-income countries. In response, through the Paris Agreement, the international community pledged to limit global warming to well below 2 degrees Celsius above pre-industrial levels. Carbon pricing has been highlighted as a crucial prerequisite for effective climate change mitigation. Carbon pricing is essentially a payment required to emit one ton of CO2 into the atmosphere. This makes production or consumption of carbon-intensive goods and services more expensive. While carbon pricing policies aim to shift behavior towards low-carbon alternatives, they can also result in unintended distributional effects for households, especially when lower-cost alternatives are not available. The negative distributional impacts can be offset through specific policy design choices, but efforts to do so should not undermine the goal of incentivizing emissions reduction.